Purchase Intention Of Generation Z Toward Global Running Shoe Brands: The Role Of Functional Value, Social Value, And Brand Awareness Using The Extended Theory Of Planned Behavior - Adawiyaha, Amaliah Robhi’atul; Efraimb, Joshua Felim; Auliac, Nabila Nurul; Hannand, Sufrin (Syntax Literate, 2025)
The rise of healthy lifestyles in Indonesia has encouraged Generation Z, particularly in the JABODETABEK area, to engage in running. Global brand running shoes are their preferred choice due to functionality, social status, and brand awareness. This research examines the factors affecting purchase intention for global brand running shoes among Generation Z by integrating the Extended Theory of Planned Behavior (ETPB) and the Theory of Consumption Value (TCV). The research model explores the effects of functional value, social value, brand awareness, attitude toward purchasing global branded running shoes, subjective norm, and perceived behavioral control on purchase intention. Data were collected through an online survey of 185 Generation Z respondents across the JABODETABEK region and analyzed using SEM-PLS with the SMART PLS application. The findings show that functional value, social value, and brand awareness significantly affect attitude toward purchasing global branded running shoes. Additionally, social value, attitude toward purchasing global branded running shoes, subjective norm, and perceived behavioral control have a direct effect on purchase intention. However, brand awareness and functional value do not significantly affect purchase intention. These findings offer theoretical insight into how the integration of ETPB and TCV helps explain Generation Z's purchase intentions for global brand running shoes.